VALERIE: A Guide to Qualitative Evaluation of Player Experience in Location-Based Games Using Interviews - Carneiro, Nayana; Viana, Windson; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
Location-based games (LBGs) differ from conventional digital games because they blur the boundaries between real and virtual worlds as they turn the physical space into part of the game scenario. Besides, LBGs have particular characteristics, such as mobility, pervasiveness, and spatiality. For their complexity and potential of new applications, LBGs pose new challenges to industry and academy, and one of these challenges lies in evaluating the player interaction with an LBG. Thus, it is necessary to create and adapt methods that allow us to evaluate player interaction considering LBGs characteristics and provide a deeper comprehension of the player experience (PX). This paper presents VALERIE (eVAluation of Location-based games and player Experience Interview guidE), a guide to qualitative evaluations of PX in LBGs through the application of semi-structured interviews. VALERIE provides a set of techniques, 60 topics, and orientations that can help students, practitioners, and researchers plan and conduct qualitative interviews for this purpose.